Employment effects of immigration to Germany in the period of migration policy liberalization, 2005–2018 - Isil Erol; Umut Unal (Eurasian Economic Review, 2022)
Germany has undergone a significant migration policy shift since the early 2000s. This paper examines the total employment effect of immigration during the liberalization of migration policies from 2005 to 2018 using a regional approach. A set of methods, along with static and dynamic macro-econometric models, were applied on a balanced panel formed by a unique and first-hand-collected data for 156 statistical regions based on the definition of the German Federal Employment Agency. We find suggestive evidence that there has been a significant adverse impact of new immigrants on the overall employment rate, and this negative effect is substantially larger than those reported in previous studies on the employment effect of immigration in the German labor market. In a further step, we divide our sample into two subsamples to capture the employment effect of the massive humanitarian inflows that began in 2015. Our results indicate that, in addition to the new immigrants' lower rate of integration into the local labor markets, a sudden influx of asylum seekers may possibly lead to a substantial fall in the employment rates, because asylum seekers are not immediately allowed to work in the country.
Keywords: J00; J15; J61; 330; Immigration; Labor market; Employment; Labor economics; Asylum seekers